For the beginning, we have to re-write each term of the expression of the function.

We'll start with x^-x*. *Since the power is negative, we'll re-write it according to the rule:

x^-x = 1/ x^x

We know also that the value of any number, raised to the 0 power, is 1. According to this x^0 = 1.

We'll re-write the expression of the function:

f(x) = 1/x^x - 1 + 2^x

To calculate f(3), we'll substitute x by the value 3.

f(3) = 1/3^3 - 1 + 2^3

f(3) = 1/27 - 1 + 8

f(3) = (1-27+8*27)/27

f(3) = (-26 + 216)/27

**f(3) = 190/27**

We know that f(x)= x^(-x)-x^0+2^x.

To find the value of f(x) for any value of x we only need to replace x in the expression for f(x).

Doing the same for x=3, we get:

f(3)= 3^(-3)-3^0+2^3

Now we know that x^(-x)= 1/(x^x) and x^0=1

Therefore f(3)= 3^(-3)-3^0+2^3= 1/(3^3)-1+8=(1/27)-1+8

=(1-27+8*27)/27

=190/27

**f(3)=190/27**

f(x) = x^x - x^0 +2^x

To find the value of f(3).

Solution:

f(x) = x^3-x^0+2^x

To get the value of f(3), we substitute x=3 in the given function.

Therefore f(3) = 3^3-3^0+2^3

f(3) 3*3*3 - 1 + 2*2*2, as 3^0 = a^0 = a^(1-1) = a/a = 1 for any number.

f(3) = 27-1+8

f(3) = 27+8-1

f(3) = 35-1

f(3) = 34.

Given:

f(x) = x^(-x) - x^0 + 2^x

Therefore:

f(3) = 3^(-3) - 3^0 + 2^3

= 1/(3^3) - 1 + 8

= 1/27 + 8

= 217/27 = 8.037